ANALISIS KETERAMPILAN GURU DALAM PENGELOLAAN KELAS PADA MATA PELAJARAN SENI BUDAYA KELAS VII DI SMP NEGERI 13 MAKASSAR - Gayatri; Farida; Abdul Hakim (STKIP Subang, 2024)
Aims to describe the teacher’s ability to carry out classroom management in arts and culture learning, as well as supporting and inhibiting factors for classroom management. The research uses qualitative research methods with a case status study type. Data collection techniques use interview, observation and questionnaire techniques. Research stages: pre-field stage, field work stage, data analysis stage, evaluation and report stage. The results of the research show that the arts and culcure teacher in class VII A of SMP Negeri 13 Makassar already understands and has quite good classroom management. Teachers show a warm and enthusiastic attitude in providing challenges in the classroom, using variety, providing reinforcement, instilling discipline, paying ettention to the physical condition of the classroom environment, being able to design a positive environment for learning and being a good communicator.